Therapists' Perceptions of School-based Mental Health Services: A Qualitative Evaluation of two Behavioral Health Models - Sheina Costa; Osayande Osagiede; Jason Rose; Kimberly A. Allen; Aaron Spaulding; Mary Rose; Emma Apatu (University of North Florida, 2017)
Therapists' perceptions of school-based mental health programs are considered to be an important factor in determining the effectiveness of a school based behavioral health model. This qualitative evaluation summarizes the perceptions of participant therapists on two different behavioral health models called Full Service Schools (FSS) and Full-Service Schools (FSS) Plus model that are currently being implemented in a large school district in Florida. FSS therapists provide therapy at a hub location whereas FSS Plus therapists work at one particular school. The study utilizes therapists' views of their respective programs to compare and contrast the effectiveness of each of the behavioral health models. Five focus groups involving 24 therapists from both models were held at five separate locations. Nvivo version 10 was used to conduct a thematic analysis of collected data. Study findings revealed better results for the FSS Plus model as compared to the FSS model in terms of successful elimination of barriers such as transportation and lack of physical space to provide therapy. This study suggests that improved and effective behavioral health services can be provided to students by assigning a designated therapist at each school.